(untitled) (Research, Society and Development, 2023)
Introduction: Meningococcal disease is characterized by bacterial infection by Neisseria meningitidis and presents it’self in different clinical forms. Meningococcal Meningitis is the most prevalent form of presentation and results from meningeal inflammation caused by hematogenous dissemination of the microorganism. Objective: To update the analysis of the epidemiological behavior of meningococcal meningitis in Brazil. Methods: Retrospective descriptive study using data from the Notifiable Diseases Information System (Sinan) about Meningococcal Meningitis, referring to the period between 2010 and the first half of 2022. Results: In Brazil, during the analyzed period, 7550 confirmed cases of meningitis meningococcal were reported. Regarding age group, individuals under 4 years of age stand out, with the highest incidence rates of the disease observed in the first year of life. There was emphasis on the occurrence of Serogroup C and on the clinical evolution, most of the individuals evolved to discharge, despite the mortality rate being significant. The southeast stood out, with approximately 59.13% of reported cases. There were 881 cases with evolution to death, about 12.33% of the reported cases. Conclusion: There was a decrease in the number of notified cases during the epidemiological years concomitantly with the admission of the meningococcal C conjugate vaccine in the national immunization program associated with the meningococcal ACWY vaccine. Due to the high mortality rate, there is, simultaneously, the need for early recognition of the disease, highlighting the importance of developing strategies aimed at controlling the disease.